Academic self-efficacy and perception of virtual education in university students during the pandemic - Arboccó de los Heros, Manuel (2023)
The pandemic situation and the restriction measures that are well known to all forced university students to adapt to the new remote or virtual modality or otherwise suspend their studies. This new modality of teaching-learning in some students was carried out satisfactorily, although in other cases, due to extrinsic factors such as the lack of technological tools to achieve adequate connectivity, and intrinsic factors such as academic self-efficacy, which is understood as the very perception of the ability to be able to carry out studies and perform satisfactorily, the results were not optimal. The present investigation, started in the year 2022, sought to describe the level of academic self-efficacy of a group of university students, as well as the perception they had about the virtual education received during the COVID-19 pandemic period. The Robles Academic Self-efficacy Scale (2019) and a survey on opinions regarding the level of satisfaction with remote education were used as a study instrument. It was found that the level of academic self-efficacy of the evaluated students is within a lower than average range; Age is a relevant factor and it showed statistically significant differences in terms of the level of academic self-efficacy, especially in the groups of students aged 27 and over. Almost half, 46.02% of the sample, considered that this modality of virtual edu m them; and finally, more than half (51.79%) prefer the so-called mixed or hybrid education.